Trends in Neuromotor Fitness in 10-to-12-Year-Old Dutch Children: A Comparison Between 2006 and 2015/2017 - Anselma, Manou; Collard, Dorine C. M.; van Berkum, Anniek; Twisk, Jos W. R.; Chinapaw, Mai J. M.; Altenburg, Teatske M. (Frontiers in Public Health, 2020)
Children with a low level of neuromotor fitness are less skilled to participate in sports activities. Moreover, lower levels of neuromotor fitness are related to adiposity, lower cardiovascular health, and poor self-esteem in children. The aim of this paper was to determine neuromotor fitness in 10–12-year-old Dutch children over a 10-year period. Test scores measured in 2015/2017 (N = 533 in 2015, N = 941 in 2017) were compared with scores of same-aged children measured in 2006 (N = 1986). Neuromotor fitness was assessed using the MOPER fitness test battery, including speed and agility, strength, flexibility, and coordination and upper-limb speed. Data were analyzed using multilevel linear regression models and tobit regression analyses in case of skewed distributions with an excess of zeros. Analyses were stratified by age and gender, and adjusted for level of urbanization. Children in 2015/2017 performed significantly worse on speed and agility (β = 0.8 to 1.1 s), significantly better on coordination/upper-limb speed (β = −1.0 to −0.6 s), and–except for 12-year-old girls–significantly worse on flexibility vs. children in 2006 (β = −3.4 to −1.8 cm). Additionally, upper-body strength was significantly worse among 10-year olds (β = −3.2 to −2.5 s) while leg strength was significantly worse among 11-year-olds in 2015/2017 vs. 2006 (β = −1.8 to −1.7 cm). Trunk strength was worse among 11- and 12-year old boys (β = 1.1 to 1.2 s). In line with a previously observed downward trend in neuromotor fitness among children (1980–2006), we found worse scores on speed and agility, and flexibility in 2015/2017 vs. 2006, stressing the need for interventions aimed at improving neuromotor fitness in order to promote physical activity and future health.